What's New in Pediatric Orthopaedic Quality, Safety, and Value? A Systematic Review With Results of the 2016 POSNA Quality, Safety, and Value Initiative (QSVI) Challenge. Issue 10 (November 2018) - Miller, Daniel J.; Cahill, Patrick J.; Janicki, Joseph A.; Stephenson, Lindsay P.; Choi, Paul D.
Abstract : Background: Enhancing the safety, quality, and value of care provided is a point of emphasis for modern health care systems. We performed a review of recent literature to highlight those efforts relevant to pediatric musculoskeletal care. Methods: We searched the PubMed database for all papers related to quality improvement, patient safety, and/or value in pediatric orthopaedics published from October 1, 2012 to October 31, 2017, yielding 193 papers. Results: A total of 36 papers were selected for review based upon new findings. Papers were selected based on significant contributions in the following categories: casting safety, antibiotic stewardship/infection prevention, perioperative care pathways, blood conservation, venous thromboembolic disease prevention, and imaging safety/appropriateness. Conclusions: There have been numerous advances in safety, quality, and value in pediatric orthopaedic care. Quality improvement efforts emphasizing provider education and safety monitoring can lead to a decrease in cast-related complications. Perioperative care pathways and bundles are associated with a decrease risk of surgical site infection and decreased length of stay in pediatric spinal deformity surgery. Increased scrutiny has been placed on the value of routine follow-up radiographs in pediatric fracture and spinal deformity care. Level of Evidence: Level 4—literature review.